An assessment of specialized instructional spaces in 'K-12 ready' senior high schools - Nobleza, Coreen Rose F.; Brasileño, Lynne I. (Quezon City College of Home Economics, University of the Philippines Diliman, 2018)
The study examined the future, fixtures and equipment (FF&E) needs of specialized instructional spaces which cater to the STEM strands in the K-12 curriculum. The Sites of the study included three- state-run senior high schools offering the Science, Technology, Engineering, and Mathematics (STEM) strand. The study used the Educational Facilities Manual (2010) from the Department of Education (DepEd) in assessing the compliance with the new curriculum of the Enhanced Basic Education Act of 2013. The study made use of the Grounded Theory approach. Data analysis included cross-referencing of emerging themes gathered from site observation of specialized instructional spaces of state-run high schools and key informant interviews with eight (8) instructors handling Biology, Chemistry and Physics subjects under the STEM strand. The study showed that thorough spaces planning and coordination of stakeholders and specialists was essential in providing ergonomically designed specialized instructional spaces. The research highlighted that building systems such as electric, plumbing, and heating, ventilation and air-conditioning systems must be planned for specialized equipment in the laboratories. Overall, the research findings emphasized that schools' infrastructure must be well-planned to support the K-12 curriculum. "K-12" readiness does not only rely with the design of the curriculum but the design of the facilities as well. In the STEM strand, the provision of functional laboratories may be considered as a prerequisite to being 'K-12 ready.' The study's approach may also be applied in assessing instructional spaces for other strands of the K-12 curriculum.
submitted June 2018
Thesis (B.S. Interior Design)--University of the Philippines Diliman
Keywords: Classrooms -- Philippines -- Designs and plans; Science rooms and equipment -- Philippines